Comment on the paper "NDSD-1000: High-resolution, high-temperature nitrogen dioxide spectroscopic Databank" by A.A. Lukashevskaya, N.N. Lavrentieva, A.C. Dudaryonok, V.I. Perevalov, J Quant Spectrosc Radiat Transfer 2016;184:205–17. (October 2017) - Perrin, A.; Ndao, M.; Manceron, L.
Highlights: It is demonstrated that the infrared NO2 line intensities included in the HITRAN and GEISA databases were generated using the correct theoretical model. An error was performed for line intensities in the NDSD-1000 high-temperature nitrogen dioxide spectroscopic databank. A high resolution Fourier transform spectrum recorded for NO2 at 6.2 µm validates the correct line intensity calculation. Abstract: A recent paper [1] presents a high-resolution, high-temperature version of the Nitrogen Dioxide Spectroscopic Databank called NDSD-1000. The NDSD-1000 database contains line parameters (positions, intensities, self- and air-broadening coefficients, exponents of the temperature dependence of self- and air-broadening coefficients) for numerous cold and hot bands of the 14 N 16 O2 isotopomer of nitrogen dioxide. The parameters used for the line positions and intensities calculation were generated through a global modeling of experimental data collected in the literature within the framework of the method of effective operators. However, the form of the effective dipole moment operator used to compute the NO2 line intensities in the NDSD-1000 database differs from the classical one used for line intensities calculation in the NO2 infrared literature [12]. Using Fourier transform spectra recorded at high resolution in the 6.3 µm region, it is shown here, that the NDSD-1000 formulation is incorrect since the computed intensities do not account properly for the (Int(+)/Int(−)) intensity ratio between the (+) (J = N+ 1/2) and (−) (J = N−1/2) electron – spin rotation subcomponents of the computed vibration rotation transitions. On the other hand, in the HITRAN or GEISA spectroscopic databases, the NO2 line intensities were computed using the classical theoretical approach, and it is shown here that these data lead to a significant better agreement between the observed and calculated spectra.